Mapping the Corrosion Behavior of AZ91D Magnesium Alloy: Influence of Chloride Concentration and Potentiostatic Polarization - Ferreira dos Santos, Regiane Cristina; Lopes de Oliveira, Mara Cristina; Altobelli Antunes, Renato (Innovations in Corrosion and Materials Science (Discontinued), 2016)
Background: AZ91D is one of the most widely used die-casting magnesium alloys. The corrosion processes of these materials is complex due to the simultaneous action of metallurgical and surfaces states. Mapping the corrosion behavior in chloride-containing aqueous solutions is of practical interest to guide the safe use of magnesium alloys against deterioration and accompany the evolution of the electrochemical response with time. Methods: The corrosion behavior was assessed using electrochemical tests consisting of potentiostatic polarization and potentiodynamic polarization for the AZ91D alloy after immersion for up to 7 days in NaCl solutions with different chloride concentrations. Results: A corrosion map was elaborated using the information obtained from the electrochemical tests. Immunity, passivation and corrosion zones were identified. The chloride concentration strongly affects the passivation range. Conclusion: The corrosion region becomes wider as the chloride concentration increases at a given applied potential. The surface oxide film is, therefore, protective in the most diluted solutions (0.01 M and 0.03 M) below -1.20 V and becomes more prone to pitting corrosion for more concentrated solutions. The corrosion map evolved from 1 to 7 days of immersion, suggesting that transition between the different zones can be affected by the exposure conditions.
Keywords: AZ91D